Late Pleistocene-Holocene planktonic assemblages in three box-cores from the Mediterranean Ridge area (west-southwest of Crete): Palaeoecological and palaeoceanographic reconstruction of sapropel S1 interval - Principato, MS; Giunta, S; Corselli, C; Negri, A (Palaeogeography, Palaeoclimatology, Palaeoecology, 2003)
Planktonic foraminiferal and calcareous nannofossil assemblages of three box-cores from the western-central part of the Mediterranean Ridge area were investigated and correlated. In particular we focused on the most significant faunal and floral signals recorded before, during and after sapropel SI deposition. The interval preceding S1 is characterised by an increasing trend of the two planktonic foraminiferal species, Globorotalia inflata and Truncorotalia truncatulinoides, that are usually related to a well developed cold and deep mixed layer. This change is supported also by the rarity of warm water coccolithophorid species and by the presence of the deep dwelling species Florisphaera profunda. The beginning of S1 is marked by the disappearance of G. inflata and T. truncatulinoides and by the significant increase in abundance of Globigerinoides ruber, especially the rosea variety usually considered indicative of warmer conditions. Warm water species increase also within the coccolithophorid assemblage, while the upwelling species Reticulofenestra spp. suddenly decreases and remains low across the whole sapropel interval. The sedimentary expression of the end of anoxia is the upper boundary of the oxidised level observed above S1 in the three box-cores. Across this boundary we detect a small but well defined increase of Braarudosphaera bigelowii, the decrease of warm water coccolithophorid species and the increase of Reticulofenestra spp. This boundary is marked also by the reoccurrence of the planktonic foraminiferal species G. inflata and Neogloboquadrina pachyderma dextral and by an evident decrease of G. ruber var. rosea, indicating the end of the Holocene Climatic Optimum and the beginning of a cold and wet phase, probably corresponding to the Atlantic-Subboreal continental transition. (C) 2002 Elsevier Science B.V. All rights reserved.